Sunan An-Nasai: Imam An-Nasai's Contribution to Compiling Hadith on Law and Etiquette - Fauzi Syam Latief (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study analyzes Sunan An-Nasa’i with a focus on its contribution to Islamic law (fiqh) and ethics, as well as the practical application of its hadiths in contemporary Muslim society. Compiled by Imam Ahmad ibn Shu'ayb An-Nasa’i, Sunan An-Nasa’i is one of the six primary hadith collections in Sunni Islam, known for its strict authenticity and focus on legal and ethical teachings. Using a qualitative approach with text analysis, this study examines hadiths related to legal principles and ethical behavior to understand their relevance in the context of modern social, legal, and political developments.This study compares the hadiths in Sunan An-Nasa’i with similar ones in Sahih Bukhari and Sahih Muslim to highlight similarities and differences in the presentation of law and ethics. The findings show that Sunan An-Nasa’i offers practical guidance on issues such as social justice, personal behavior, marriage, transactions, and public ethics. These hadiths remain relevant in the modern world, addressing challenges such as the integration of Islamic values into national legal systems and ethical dilemmas arising from technological advancements and globalization.This study emphasizes the importance of integrating these teachings into Islamic education and contemporary legal practice to promote justice, equal ity, and ethical conduct in the Muslim community.